Revisiting the moderating effect of speaker proficiency on the relationships among intelligibility, comprehensibility, and accentedness in L2 Spanish - Huensch, Amanda; Nagle, Charlie (Studies in second language acquisition, 2023)
This report examines the potential impacts of task and proficiency on listener judgments of intelligibility, comprehensibility, and accentedness in L2 Spanish. This study extends Huensch and Nagle [Language Learning, 71, 626–668, (2021)], who explored the partial independence among the global speech dimensions for speech samples taken from a picture narrative task. Given that the type of speaking task used to elicit speech samples has been shown to impact the strength of the linguistic features contributing to the global speech dimensions and to explore the impact of task on the relationships among the dimensions, the current study followed the same procedure as Huensch and Nagle but employed a task in which participants responded to a prompt based on NCSSFL-ACTFL Can-Do Statements. The speech samples were elicited from instructed L2 Spanish learners of varying proficiency (n = 42) and were rated by a group of native-speaking Spanish listeners (n = 80) using Amazon Mechanical Turk. In general, the results were consistent with those reported in the initial study indicating a significant, positive, and consistent relationship between comprehensibility and intelligibility and a null relationship between accentedness and intelligibility. The limited differences between the studies’ findings are discussed considering the potential impact of task.